Pembentukan Identitas Budaya melalui Kepakaran Artistik dalam Film dan Televisi sebagai Sarana Representasi Sosial dalam Masyarakat - Nugroho, Heri; Patrio, Andri Nur (Pusat Riset dan Inovasi Nasional, 2025)
Film and television play a central role in shaping and representing the cultural identity of society. Through artistic expertise manifested by directors, screenwriters, actors, cinematographers, and producers, cultural construction is presented not only as entertainment but also as a social discourse that reflects values, traditions, and the dynamics of collective identity. This study aims to analyze how artistic expertise contributes to constructing cultural identity representation through film and television mediums in Indonesia. The research methodology used is qualitative, employing content analysis and semiotics approaches on selected Indonesian films and TV series that highlight cultural aspects, such as Losmen Bu Broto and Gadis Kretek. These works were chosen because they feature rich local culture while reflecting the role of culture in the dynamics of Indonesian society. The findings indicate that artistic expertise plays a crucial role in constructing cultural representation, both through narrative, visual elements, music, and actors' performances. The representations produced not only affirm local and national identities but also reflect the process of cultural negotiation with global influences. This study underscores that film and television serve as strategic media for cultural diplomacy and the formation of collective identity awareness in Indonesian society. Through this process, these mediums contribute to the preservation of local culture amidst global cultural flows. The research highlights the importance of film and television as tools for maintaining and constructing cultural identity, where local traditions and values are both preserved and adapted to the changing global landscape.